‘He crossed and re-crossed the way repeatedly’: Illegible Crossings in Poe’s ‘The Man of the Crowd’ - Estelle Murail (Cahiers Victoriens et Edouardiens)
This article proposes to reread Poe’s short story ‘The Man of the Crowd’ through the prism of the Baudelairean word croisement or ‘crossing’. Poe’s London-set tale famously crossed the Channel to inform Baudelaire’s visions of Paris, but this traffic of influences goes both ways. The Baudelairean word croisement, enriched by its crossings with French texts and contexts, condenses several meanings which can shed light on Poe’s story. It designates a certain way of occupying space, and when applied to human relations, it can evoke (dis)connections. As a textual term, it can refer to the workings of intertextuality. This combination of spatial, social, and textual connotations makes it relevant to ‘The Man of the Crowd’. The sense of illegibility which pervades this enigmatic tale stems from these different forms of croisements. Both narrator and reader are confronted with the fear of not being able to read the many crossings at work in the (urban) text, which turns them into detectives on an endless hermeneutic journey. Indeed, the tale constantly seeks to involve us in hermeneutic crossings which shape the text, and thus forces us to ‘cross and re-cross the way repeatedly’.